2019
DOI: 10.3389/fncel.2019.00500
|View full text |Cite
|
Sign up to set email alerts
|

Brainiac Caspases: Beyond the Wall of Apoptosis

Abstract: For the last two decades, caspases, a family of cysteine-aspartic proteases, have evolved from being considered solely as regulators of apoptosis or inflammation to having a wider range of functions. In this mini review, we focus on the most recent “non-apoptotic” roles of caspases in the CNS, particularly in neurons, astrocytes and oligodendrocytes. Non-apoptotic caspase functions in microglia have already been reviewed extensively elsewhere. Here we discuss the involvement of caspases in the activation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 84 publications
1
22
0
Order By: Relevance
“…Finally, we confirmed in RA-SH-SY5Y cells the H 2 O 2 potency to induce ICE-like protease, caspase-1 activity (Jantas et al 2018a) which was significantly attenuated only by Nec-1 + Curc combination (Table 3). Activation of this enzyme participates in another form of cell damage, namely pyroptosis (Espinosa-Oliva et al 2019;Wang et al 2019). Since previous data showed the activation of this proinflammatory protease in neuronal cell type, including SH-SY5Y cells and neuroprotective potency of its inhibitors (Chen et al 2019;Knaryan et al 2014;Nath et al 1996;Zhao et al 2019a, b), it is highly probable that this mechanisms could be responsible for synergistic protective action of Nec-1 and curcumin against H 2 O 2 -evoked cell damage, observed in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…Finally, we confirmed in RA-SH-SY5Y cells the H 2 O 2 potency to induce ICE-like protease, caspase-1 activity (Jantas et al 2018a) which was significantly attenuated only by Nec-1 + Curc combination (Table 3). Activation of this enzyme participates in another form of cell damage, namely pyroptosis (Espinosa-Oliva et al 2019;Wang et al 2019). Since previous data showed the activation of this proinflammatory protease in neuronal cell type, including SH-SY5Y cells and neuroprotective potency of its inhibitors (Chen et al 2019;Knaryan et al 2014;Nath et al 1996;Zhao et al 2019a, b), it is highly probable that this mechanisms could be responsible for synergistic protective action of Nec-1 and curcumin against H 2 O 2 -evoked cell damage, observed in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…Caspases are a family of endonucleases that act as critical links in the molecular networks that control apoptosis and play critical roles in the induction of apoptosis as both initiators (caspase-2, -8, -9, -10, 20, and -22) and executioners (caspase-3, -6, -7, and 21) [ 50 , 51 ]. Caspases are initially expressed as inactive procaspases that are activated by pro-apoptotic signals via proteolytic cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the caspase family plays an important role in apoptosis execution ( Wang et al, 2019 ). Caspase-3 constitutes the central molecule in apoptosis and is involved in three main pathways: the exogenous death receptor pathway, endogenous mitochondrial pathway, and endoplasmic reticulum pathway ( Espinosa-Oliva et al, 2019 ). The exogenous death receptor pathway is triggered by a transmembrane protein reaction caused by TNF-α, and mainly involves caspase-8, a pro-apoptotic factor ( DeLaney et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%